Verplichte Overheidszaken Principle on the Perspective of Covid-19 Vaccination in Indonesia - I Nyoman Prabu Buana Rumiartha (Focus Journal : Law Review, 2021)
That the outbreak of Covid-19 in December 2019, made the entire world community feel the impact of the spread of the covid-19 virus. The COVID-19 pandemic poses a big challenge for the government of a country in an effort to improve the health status of the community, one of which is Indonesia. The government is trying to break the chain of disease transmission through vaccination efforts to prevent Covid-19 infection. The Covid-19 vaccination law policy in Indonesia related to Presidential Regulation of the Republic of Indonesia Number 14 of 2021 concerning Amendments to Presidential Regulation Number 99 of 2020 concerning Vaccine Procurement and Vaccination Implementation in the Context of Overcoming the Corona COVID-19 Pandemic (Perpres 14 2021) has been issued by President. The Covid-19 vaccination aims to reduce the transmission or contagion of COVID-19, reduce morbidity and mortality due to COVID-19, achieve group immunity in the community, and protect the community from COVID-19 in order to remain socially and economically productive. Covid-19 vaccination during a pandemic is a Public Goods effort carried out by the Government as an Obligatory Public Health Functions, therefore all vaccination costs must be fully borne by the government as in line with the Verplichte Overheidszaken Principle in a country in organizing and or run the government.